PERAN STRATEGIS PENERAPAN KONSEP SISTER CITY DALAM MENCIPTAKAN SURABAYA GREEN-CITY - Inggang Perwangsa Nuralam (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
Indonesia has many big cities with dynamic urbanization trend, increased economic growth and activities, rapid population growth, and dense populations such as Jakarta, Bandung, Medan, Surabaya and Balikpapan. As a result, the complex activities of people in urban areas need space and these needs cause environmental degradation, such as the practice of throwing garbage that is not in place. To prevent this in the future, it is important for developing countries like Indonesia to have benchmarks. Benchmarks for developing countries can come from developed countries. So far inter-city development usually has partnerships with cities abroad, including the sister city concept. Sister city practices can be used by cities in Indonesia for the development of good practices. The collaboration of Surabaya (Indonesia) with Kitakyushu (Japan) focuses a lot on creating urban planning that is environmentally sound or commonly known as green city or eco-city.